Pengembangan Modul Ajar Interaktif Berbasis Differentiated Instruction Untuk Mengakomodasi Keberagaman Kemampuan Pemecahan Masalah Matematis Siswa - Zahra Mahdiyyah; Yudi Darma; Rahman Haryadi (cendekia citra gemilang, 2026)
Mathematics learning in schools still faces obstacles in the form of diversity in students' mathematical problem-solving abilities that have not been optimally accommodated in the learning process. This study aims to develop an Interactive Teaching Module based on Differentiated Instruction for geometry material for seventh-grade students at MTs Mujahidin Pontianak and to determine its level of validity, practicality, and effectiveness. The study used the Research and Development method with a 4D development model modified into 3D, including the define, design, and develop stages. The research subjects consisted of four expert validators and 30 seventh-grade students as trial subjects. Data were collected through validation sheets, teacher and student response questionnaires, and mathematical problem-solving ability tests. The results showed that the module obtained a very valid category with an average of 94.7%; very practical, based on teacher responses of 93.33% and students of 85.58%; and effective, with an average posttest of 71.67 and learning completeness of 66.67%. The research findings show that the Interactive Teaching Module based on Differentiated Instruction is suitable for supporting adaptive, interactive mathematics learning and is oriented towards developing students' mathematical problem-solving abilities in line with diverse learning abilities.